2002
DOI: 10.4049/jimmunol.168.11.5900
|View full text |Cite
|
Sign up to set email alerts
|

HER-2/neuand hTERT Cryptic Epitopes as Novel Targets for Broad Spectrum Tumor Immunotherapy

Abstract: Tolerance to tumor-nonmutated self proteins represents a major obstacle for successful cancer immunotherapy. Since this tolerance primarily concerns dominant epitopes, we hypothesized that targeting cryptic epitopes that have a low affinity for HLA could be an efficient strategy to breach the tolerance to tumor Ags. Using the P1Y heteroclitic peptide approach, we identified low affinity cryptic HLA-A*0201-restricted epitopes derived from two widely expressed tumor Ags, HER-2/neu and hTERT. The P1Y variants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(80 citation statements)
references
References 40 publications
2
78
0
Order By: Relevance
“…This is not surprising, because vaccinating mice or patients with solely MHC-I tumor epitopes has produced only modest results in most studies. For some Ags, altering the wild-type MHC-I epitope so that it binds more strongly to MHC and/or demonstrates greater recognition in vitro by Ag-specific T cells improves the immunization potential and the clinical outcome (54,(65)(66)(67). In this study, we show that vaccinating FVB/N mice with dendritic cells pulsed with a heteroclitic variant of the wild-type epitope also induces improved protection against tumors that express the natural RNEU 420 -429 epitope as compared with immunization with the RNEU 420 -429 epitope itself.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, because vaccinating mice or patients with solely MHC-I tumor epitopes has produced only modest results in most studies. For some Ags, altering the wild-type MHC-I epitope so that it binds more strongly to MHC and/or demonstrates greater recognition in vitro by Ag-specific T cells improves the immunization potential and the clinical outcome (54,(65)(66)(67). In this study, we show that vaccinating FVB/N mice with dendritic cells pulsed with a heteroclitic variant of the wild-type epitope also induces improved protection against tumors that express the natural RNEU 420 -429 epitope as compared with immunization with the RNEU 420 -429 epitope itself.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that T cells of the human immune system can recognise hTERT peptides, and a number of HLA-class I and class II epitopes have been characterised (Vonderheide et al, 1999;Minev et al, 2000;Arai et al, 2001;Vonderheide et al, 2001;Hernandez et al, 2002;Scardino et al, 2002;Schroers et al, 2002Schroers et al, , 2003Gross et al, 2004). Recently it has also been reported that telomerase-specific CD4 þ and CD8 þ T-cell responses are induced upon vaccination with hTERT-transfected dendritic cells (Su et al, 2005).…”
mentioning
confidence: 99%
“…[7][8][9][10] Recently, several results regarding hTERT-specific cytotoxic T cell (CTL) responses were reported for humans and mice. [11][12][13][14][15][16][17][18][19][20] These reports revealed that hTERT-specific CTLs induced by stimulation with peptides or DNA-based immunization kill cancer cell lines that have high levels of hTERT, suggesting that hTERT-reactive T cell clones are not deleted from the human T cell repertoire and that hTERT may be a useful tumor-specific antigen as a target for T-cell-based immunotherapy for cancers. However, the existence of hTERT-specific CTLs and the relationship between immunological…”
mentioning
confidence: 99%